Checklist of the springtails (Hexapoda: Collembola) of the Edough massif, northeastern Algeria - Brahim-Bounab, Hayette; Bendjaballah, Mohamed; Hamra-Kroua, Salah; Lachi, Noureddine; Bedos, Anne; Deharveng, Louis (Zootaxa, 2020)
Based on 225 samples taken from different biotopes in the Edough Massif (northeastern Algeria) from 1998 to 2018, we compiled a list of 91 collembolan species names from the literature, of which 72 can be considered valid records. Fourteen of them are only known from this massif in Algeria, and eight are endemic of northeastern Algeria. These 72 species are spread over 14 families and 49 genera. The family Neanuridae is the most diverse with 18 species, including six species of the genus Friesea. The monotypic genus Edoughnura (Neanurinae) is endemic to the Edough and Collo massifs. Several of the listed species do not fully match the diagnosis of the species to which they have been assigned and may represent undescribed taxa. Entomobryidae as well as several habitats (epigean, deep soil, littoral) remain unsampled or undersampled in Edough, and are likely to host many more species than those listed in this paper.